2020
DOI: 10.1186/s12886-020-01415-y
|View full text |Cite
|
Sign up to set email alerts
|

Effect of corneal cross-linking on endothelial cell density and morphology in the peripheral cornea

Abstract: Background: To compare the endothelial cell density and morphology in the peripheral cornea before and after corneal cross-linking (CXL). Methods: This study evaluated thirty-one eyes of 31 patients who were treated with standard CXL for progressive keratoconus. Preoperatively and 6 months postoperatively, we compared the corneal endothelial cell density (ECD), the coefficient of variation in cell size (CV), and the percentage of hexagonal cells (HEX), in the peripheral regions of the cornea, using a non-conta… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 23 publications
0
1
0
Order By: Relevance
“…The assessment of endothelial cell density (ECD) loss in standard and accelerated and transepithelial CXL protocols in the pediatric group has not produced a statistically significant decrease in ECD after the procedure [ 21 , 23 , 56 , 58 , 61 , 69 , 70 , 76 , 80 , 82 , 96 , 97 ]; however, other studies reported that, depending on the protocol and carrier used, there is damage to endothelial cell density [ 68 , 98 100 ]. In a retrospective SCXL study developed by Barbisan et al in 2020, involving 105 eyes, a statistically significant reduction in ECD was observed, as well as corneal thinning after 1 year of follow-up, evidencing the potential impact of CXL on anatomy and corneal physiology [ 68 ].…”
Section: Resultsmentioning
confidence: 99%
“…The assessment of endothelial cell density (ECD) loss in standard and accelerated and transepithelial CXL protocols in the pediatric group has not produced a statistically significant decrease in ECD after the procedure [ 21 , 23 , 56 , 58 , 61 , 69 , 70 , 76 , 80 , 82 , 96 , 97 ]; however, other studies reported that, depending on the protocol and carrier used, there is damage to endothelial cell density [ 68 , 98 100 ]. In a retrospective SCXL study developed by Barbisan et al in 2020, involving 105 eyes, a statistically significant reduction in ECD was observed, as well as corneal thinning after 1 year of follow-up, evidencing the potential impact of CXL on anatomy and corneal physiology [ 68 ].…”
Section: Resultsmentioning
confidence: 99%